Wheeze and Food Allergies in Children Born via Cesarean Delivery: The Upstate KIDS Study. Issue 2 (26th November 2018) - Adeyeye, Temilayo E; Yeung, Edwina H; McLain, Alexander C; Lin, Shao; Lawrence, David A; Bell, Erin M
Abstract: We examined whether cesarean delivery (CD) increased the risk of wheeze or food allergy in early childhood compared with vaginal delivery and whether these associations were mediated by breastfeeding. The study population was the Upstate KIDS cohort (2008–2010) of mothers and infants from the State of New York (excluding New York City). Infant's wheeze was reported by questionnaire every 4–6 months until 3 years of age, as were food allergies beginning at 8 months. Modified Poisson regression was used to compare risks of the outcomes according to mode of delivery (MOD). Potential confounders were identified a priori using directed acyclic graphs. Emergency CD ( n = 1, 356) was associated with elevated risk of wheeze, adjusting for pregnancy complications, maternal atopy, gestational age, birth weight, and smoking during pregnancy (risk ratio = 2.47, 95% confidence interval: 1.31, 4.66), and an increased risk of food allergy, adjusting for maternal atopy, prepregnancy body mass index, smoking during pregnancy, and parity (risk ratio = 3.02, 95% confidence interval: 1.26, 7.25). Neither outcome was significantly associated with planned CD ( n = 1, 565 infants). Breastfeeding mediated the association between MOD and wheeze but not food allergy. Other factors not associated with early-life microbial transfer, but relating to the development of the outcomes, might contribute to the association between MOD and wheeze/food allergy.